Heidegger, Dilthey, and the crisis of historicism - Bambach, Charles R. (Cornell University Press, 1995)
Bambach's account of the demise of historicism within the context of German metaphysics provides a new perspective on the development of Heidegger's concept of ""historicity"" and on the origins of postmodern thought.